Componentes nitrogenados: metodologias analíticas e associação com outros indicadores de qualidade do leite cru refrigerado - Eduardo Goncalves Esteves (2005)
Being necessary to adjust the raw milk quality to physical, chemical and microbiological standards from the new brazilian legislation in force and from the processor establishments, indirect techniques with higher analytical capacity, following the examples taken from other countries, have been put into practice. In order to carry out this study, two hundred bulk milk samples from dairy farms situated in Minas Gerais were collected and analyzed. The milk protein, which is generally regarded as the milk component with highest value in payment for quality systems, was analyzed comparatively by the Kjeldahl and mid-infrared methods, from which the respective results for the Sr were 0.0124 and 0.0106% wt/wt, the averages were 3.113% wt/wt and 3.095% wt/wt, with a standard deviation of 0.168 and 0.171% wt/wt. The average results were found to be 26.06 mg/100g of non protein nitrogen, 5,35% of non protein nitrogen into total nitrogen, 3,113% wt/wt of crude protein analysed by Kjeldahl and 3.095% wt/wt by mid-infrared method, 2.95% wt/wt of true protein, 3.46% wt/wt of fat, 4.55 % wt/wt of lactose and 12.08 % wt/wt of total solids. The geometric average result for somatic cells count was 346,500 cells/mL and for enumeration of microrganisms was 153,500 CFU/mL. A prediction linear model for the true protein content in milk in function of the crude protein content was established, in order to be useful for dairy processing industries. The regression curve calculated from crude protein contents obtained by the reference (Kjeldahl) and indirect mid-infrared methods was evaluated, resulting in significant deviations of the intercept, the slope and the centre of gravity of the results. The association among milk components and production levels of the farms was evaluated. Concerning to the effect of the addition of urea to milk in the mid-infrared spectrometric crude protein results (fraud hypothesis), significative interferences were detected in the analytical results